On Classifications of Normal and Osculating Curves in 3-dimensional Sasakian Space - Kulahci, Mihriban Alyamac; Bektaş, Mehmet; Bılıcı, Ahmet (My University, 2019)
This study provides the definition of normal and osculating curves in 3-dimensional Sasakian space withtheir characterizations. Furthermore, the differential equations obtained from these characterizations aresolved and their figures are presented in the text.
Keywords: Fizik; Matematik